Case report: Hyperosmolar hyperglycemic syndrome secondary to PEG-asparaginase-induced hypertriglyceridemia and pancreatitis - Mudd, Todd William; Fox, Ashley Danielle; Ghaly, Mark; Keruakous, Amany (Frontiers in Oncology, 2023)
PEG-asparaginase is an established treatment of acute lymphoblastic leukemias that exhibits an antitumor effect by depleting asparagine, an amino acid essential for leukemia cell protein synthesis. Pancreatitis with hypertriglyceridemia is a well-established toxidrome associated with PEG-asparaginase. However, impaired pancreatic synthetic function and hormone release have rarely been reported as a result of PEG-asparaginase pancreatitis. In this report, we present a 22-year-old female recently diagnosed with T-acute lymphoblastic leukemia (T-ALL), who presented to the hospital with progressive weakness, confusion, blurry vision, hallucinations, and abdominal pain after induction treatment with daunorubicin, vincristine, PEG- asparaginase, and dexamethasone following AYA protocol. She was found to have hypertriglyceridemia, acute pancreatitis, and hyperosmolar hyperglycemic syndrome. While pancreatitis and hypertriglyceridemia represent commonly reported side effects of PEG-asparaginase, HHS related to these conditions has been scantly reported. Providers should maintain awareness for this association and consider routine serial glucose monitoring of patients receiving PEG-asparaginase.